Evaluasi Penerangan Jalan Umum Salaman - Borobudur Dalam Mendukung Candi Borobudur Sebagai Kawasan Strategis Pariwisata Nasional - Zaenal Arifin; Sapto Nisworo; Deria Pravitasari (CV. Ulil Albab Corp, 2022)
The focus of this research is to evaluate public street lighting on the Salaman – Borobudur section. The expected goal is to evaluate the lighting of the Salaman - Borobudur public road so that it meets the standards, provides comfort, security, traffic safety for road users, and adds to the aesthetic value of the road environment. The results of the evaluation of street lighting show that the average illuminance value produced by the LPJU does not comply with SNI 7391 : 2008 and the electricity consumption of the LPJU shows waste. Recommendations suggested to overcome this are the replacement of LPJU and pedestrian lights, replacement of LPJU controls with timers, and load discrimination based on hours of operation of pedestrian lights. The simulation results for selecting LPJUs using NIKKON LED 60 Watt lamps produce a strong light of 6.47 lux with a glare barrier of 9% for LPJUs with a 3 m pole arm and 6.52 lux with a glare barrier of 10% for LPJUs with a 1.8 m mast arm, and 2.11 lux for pedestrian lighting using 2 Watt Philips LED lamps is in accordance with SNI 7391: 2008. The energy saving potential from the recommendations suggested in a year is 71,577.96 kWh or 61.57%. The estimated initial investment cost to implement the recommendations is Rp. 629,613,400.00 with a payback period of 7 years for a project period of 20 years.